Asthma and COPD Patients' Perception of Appropriate Metered-Dose Inhaler Technique - Wijdan H. Ramadan; Aline Sarkis; Sandrine Sarine Aderian; Aline Milane (SAGE Publishing, 2020)
Objectives: Asthma and chronic obstructive pulmonary disease (COPD) are chronic illnesses of the airways affecting a good number of people in Lebanon and the Middle East. Pressurized metered-dose inhalers (pMDIs) are important drug delivery systems used to treat such pulmonary diseases. Drugs proven to be valuable and effective may fail to act effectively if such inhalers are used incorrectly. The purpose of this study was to assess the technical use of pMDIs by patients with pulmonary diseases presenting to the community pharmacies in Lebanon. Methods: A structured questionnaire was developed to collect data. A total of 601 patients using drugs delivered through pMDIs and presenting to 12 Lebanese community pharmacies were recruited to participate in the research project. The questionnaire items were divided into 3 subscales: subscale 1-assessing the device preparation; subscale 2-investigating the device use; and subscale 3-examining the knowledge and use of spacers. After confirming the reliability and validity of the survey tool, patients' responses were analyzed and compared according to many variables. Results: Many patients answered inaccurately to questions assessing both the device preparation and use. Around 40% of patients said they do not coordinate the inhalation with pressing the canister down. The mean scores were 1.72 (± 0.73) over 6 and 5.67 (± 1.44) over 7 for subscales 1 and 2, respectively. The mean total score on all questions was 7.39 over 13, with a standard deviation of 1.75. While patients' age did not impact the results, asthmatic, well-educated, male patients had fewer wrong answers when it comes to preparing and using the device ( P < .01). Conclusions: Our study showed that many patients with asthma and COPD might not be properly using their pMDIs. Appropriate inhaler use is crucial for successful pulmonary disease management. As pMDIs are one of the most difficult devices to use, proper and tailored instructions should be given to patients.